Marco Civil da Internet and the Future of Social Media Regulation in Brazil: the Impact of Courts on Platform Policy - Hartmann, Ivar Alberto; Kira, Beatriz (AoIR Selected Papers of Internet Research, 2026)
This paper examines the STF’s pending ruling on the constitutionality of Article 19 of the MCI—the cornerstone provision establishing the intermediary liability regime in Brazil—against the wider legal and policy context. Through analysis of the legal framework against which the STF will make a decision—including examining the opinions that three out of eleven Justices have already handed down—and broader political economy considerations, we address the following research question: what impact will the Supreme Court’s forthcoming decision have on the future of platform regulation in Brazil? Overall, we will argue that while the STF’s ruling on the constitutionality of the MCI’s intermediary liability regime will significantly impact the future of platform regulation in Brazil, it represents just one component of a necessary broader (and urgent) reform agenda. Overarching platform governance in Brazil has historically been shaped by Congress with lower courts constantly weighing in on the legality of different types of content. The ruling will mark the first time the STF decides on a key platform regulation disposition with systemic impact. Our conclusions hold important implications for both scholarly understanding of platform governance and practical approaches to regulatory reform, particularly in the Global South. The Brazilian case offers valuable insights for other jurisdictions grappling with similar challenges, especially in contexts of political polarisation and limited regulatory capacity.